Disease progression and adverse events in patients listed for elective percutaneous coronary intervention. Issue 957 (5th July 2005) - Talwar, S; Karpha, M; Thomas, R; Vurwerk, C; Cox, I C; Burrell, C J; Motwani, J G; Gilbert, T J; Haywood, G A
Abstract : Objective: To record disease progression and the timing of adverse events in patients on a waiting list for elective percutaneous coronary intervention (PCI). Design: Observational prospective study. Settings: A UK tertiary cardiothoracic centre, at a time when waiting lists for PCI were up to 18 months. Patients: 145 patients (116 men, median age 59.5 years) placed on an elective waiting list for PCI between October 1998 and September 1999. Main outcome measures: Adverse events recorded were death, myocardial infarction, need for urgent hospital admission because of unstable angina, and need for emergency revascularisation while waiting for PCI. Results: During a median follow up of 10 months (range 1–18 months), nine (6.2%) patients experienced an adverse event. Eight (5.52%) patients were admitted with unstable angina as emergencies. One was admitted with a myocardial infarction. Twenty nine (20.0%) patients had significant disease progression at the time of the repeat angiogram before PCI. In 10 (7%), disease had progressed so that PCI was no longer feasible and patients were referred for coronary artery bypass graft. Sixteen (11%) were removed from the PCI waiting list because of almost complete resolution of their anginal symptoms. Conclusion: Adverse coronary events and clinically significant disease progression occur commonly in patients waiting for PCI. Despite the presence of severe coronary lesions, myocardial infarction was rare and no patients died while on the waiting list. Resolution of anginal symptoms was also comparatively common. The pathophysiology of disease progression frequently necessitates a change in the treatment of patients waiting for PCI.